"Diabetes" - Causes And Complications- A Biochemical View Point - JUHI AGGARWAL; MAYUR KUMAR; PALLAVI KUMARI (International Journal of Pharma and Bio Sciences, 2012)
Diabetes Mellitus is a metabolic disorder in which glucose is underutilized, producing hyperglycemia. Diabetes is now described as one of the main threats to human health in 21st century because of the role of the lifestyle factors such as diet and obesity along with genetic factors. Due to genetic susceptibility at early age, type 2 diabetes mellitus is considered as an emerging and significant problem in children and adolescents. Once this disease is established, it leads to complications related to oxidative stress which deals with imbalance between the generation of reactive oxygen species and antioxidant defense capacity of the body. This review aims to summarize the mechanisms of increased oxidative stress, obesity and gene regulation in the causes and complications of diabetes.